Analisis Terhadap Premium Remedium Terkait Sanksi Hukum Lingkungan - Junimart Girsang; Ampuan Situmeang; Rumbadi Rumbadi (Fakultas Hukum, Universitas Internasional Batam, 2014)
Batam Island as Port and Free Trade area in accordance with Law No. 27 Year 2007 and Government Regulation No. 1 of 2007. Batam as Trade and Free Port areas including islands Watch, Setokok Island, Nipah, rempang, Galang Island, Pulau Galang The new, benefits of the implementation of the free trade zone and port 34 countries have invested in sini.Konsekuensi status Free Trade Zone is the number of investors who have a negative impact on the one hand, and the positive impact on the other side.The negative impact is environmental damage as a result of the operations of these companies, there are companies that produce hazardous toxic waste (B3), there was a company importing B3 waste into Indonesia such as PT. Jace Octavia Mandiri. Stockholm Convention of 1972, the Basel Convention on the Control of Trans boundary Movement on Hazardous Waste and Their Disposal. Indonesia ratified the Stockholm Convention was issued Law No. 32 of 2009 on the Protection and Environmental Management replaces Law Number 27 Year 1997 on Environmental Management.Batam City Government faced with a difficult choice in the application of sanctions in accordance with Law No. 32 of 2009 on the Protection and Management of the Environment, because in that regulation, administrative sanctions (ultimum Remedium) environment must be put forward before stepping other sanctions that sanctions Criminal (Premium Remedium ).